Sustainable Li-Ion EV Battery Recycling in Nepal: A Techno-Economic and Forecast-Based Approach - Khadka, Siddhartha; Bhattarai, Nawraj; Devkota, Lochan Kendra (Journal of Advanced College of Engineering and Management, 2025)
The swift uptake of electric vehicles in Nepal brings about both benefits and difficulties in terms of managing waste from lithium-ion batteries This study conducts a thorough evaluation of the practicality of setting up a Li-Ion Battery recycling facility in Nepal, encompassing predictive models, forecasting techniques, and a technical-economic analysis. This research predicts the widespread acceptance of electric vehicles by employing Compound Annual Growth Rate (CAGR) models with growth rates of 10% and 20%, examines the creation of battery waste, and performs a techno-economic assessment for a proposed lithium-ion battery recycling facility. Assessing financial viability involves determining capital expenditures (CAPEX), operational expenses (OPEX), and revenue generated from recycling materials. The selection of the best recycling technology is determined using the Analytic Hierarchy Process (AHP). The objective of the study is to provide guidance to policymakers and investors in regards to sustainable battery recycling options. Our research offers a systematic framework for policymakers and business leaders to implement environmentally friendly recycling practices that will aid Nepal's shift towards renewable energy.